Decision Support System for Internship Using Multifactor Evaluation Process (MFEP) Method Case Study: Department Of Computer and Informatics Engineering Bandung State Polytechnic - Yuliani, SY.; Aprilio, Pajri; Lestari, Sri; Syukriyah, Yenie (CENTRAL ASIA AND THE CAUCASUS, 2022)
Practical work is to apply the knowledge that has been gained during college in cases that exist in the institution or company that you want to go to. This research was conducted based on internship program that is held every year in Informatics Engineering, Bandung State Polytechnic. The internship coordinator does data collection from Internship Company or from students every year. Problems the data collected by the competence of companies receiving practical work, namely regarding and quotas that have not been recorded properly. Meanwhile interest and competence are collected from students. There are a lot of companies and student that needs to be mapped to meet company and student needs. Therefore, in this research a Decision Support System for Decision Support System for Internship at Department of Computer and Informatics Engineering Bandung State Polytechnic Using Multifactor Evaluation Process (MFEP) Method is created. It is an interactive system that is used to help making decision on internship placement by giving weight on student competence and competence that is required by company. From this research, student internship placement that is ordered by most matched competence that is required by the companies can be obtained. From the MEFP the highest and the lowest TBE is obtained. The highest TBE is 17 obtained by calculation on Karl Coombes that is assigned to CV Melani Narpati. Meanwhile the lowest TBE is 6 obtained by calculation on Marsha York, Amina Santana, Gabrielius, Kylo Thorne, Siobhan Salinas, and Jamel Orozco that is assigned to CV Mayasari.